Bridging worlds: an integrative framework for deep learning and ethnoscience in elementary IPAS education - I Ketut Dipayana; I Made Ari Winangun; I Ketut Suparya (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Elementary education in Indonesia continues to grapple with pervasive rote memorization practices in IPAS (Ilmu Pengetahuan Alam dan Sosial/science and social studies) instruction that result in students' superficial conceptual understanding. This integrative literature review examined how the integration of deep learning pedagogy and ethnoscience perspectives functions as conceptual bridges for meaningful IPAS comprehension. Following Whittemore and Knafl's (2022) methodology, 42 empirical studies published between 2018 and 2025 were synthesized from Scopus, ERIC, Google Scholar, Garuda, and SINTA databases. Consistently reported across studies, three transformative mechanisms were identified: (1) cognitive anchoring through culturally familiar local phenomena such as subak irrigation systems (evidenced in 28 of 42 studies), (2) dialogic knowledge co-construction grounded in Tri Hita Karana philosophy (19 studies), and (3) metacognitive awareness development through reflective inquiry (15 studies). The resulting integrative framework offers theoretically grounded pathways for designing IPAS instruction that promotes conceptual change rather than factual accumulation, supporting Kurikulum Merdeka implementation.